The Influence of Learning Styles, Motivation, and Types of School on Students’ English Achievement at Junior High Schoolsin Bandar Lampung - Harpain HARPAIN (International Conference on Education and Language (ICEL), 2014)
This research aims to find out whether there is any significant interaction between motivation and learning style on students’ English achievement in Bandar Lampung. This research is a non-experimental study with variant analysis study. The research is implemented at junior high schools in Bandar Lampung involving 430 students from schools categorized as public schoosl with high rating, private schools with high rating, public schools with lower rating, and private schools with lower rating. The variables consisting of one dependent variable, that is the students’ English Achievement (Y), two independent variables: motivation (X1) and learning styles (X2), and one intervention variable:  types of school (Z1)Data for students’ English achievement were taken by giving a set of test in which validity and reliability are tested. Data for motivation and learning styles were taken from students’ reponses to multiple choice questionnaire each consisting of 40 questions.The results of the analysis show: a) there is no significant interaction between motivation and learning styles on students’ English Achievement. This means that the combination of motivation and learning styles cannot distinguish between high achieving students and the lower ones. b). Learning styles have significant influence on students’ English achievement. Students with different learning styles have different English achievement. c). Motivation does not have significant influence on students’ English achievement. Students with different motivation did not have different result of English achievement.d) Types of school have a significant effect on the students’ English achievement